A Usage of McCall's Software Quality Analysis on the Bonus System of PT Surya Pratama Alam - Maria Ulfah Siregar; Ahmad Hasan Arif (JISKA (Jurnal Informatika Sunan Kalijaga), 2018)
This research is to analyse the software quality of the Bonus System of PT Surya Pratama Alam Yogyakarta. The goal of this study is to determine the level of users’ satisfaction in the use of the system. Method of analysis used is McCall method which is based on operation products with usability factors. The metrics used are Operability metrics and Training metrics. In the operability metrics, the researchers refer to the J.R. Lewis Questionnaires.  Based on the conducted research, researchers can state that the results of software quality measurements of the Bonus System of PT Surya Pratama Alam Yogyakarta is 74.72 % with standard deviation ±14.39 % for Operability metrics and 4.41 seconds with standard deviation ± 1.36 seconds for Training metrics. Based on these two metrics, it can be concluded that the Bonus System of PT Surya Pratama Alam Yogyakarta already has good usability value.